Pemanfaatan Hewan sebagai Obat Tradisional pada Masyarakat Kualu Pekanbaru dalam Kajian Ethnozootherapy - Ifada, Hanif Syifa; Husain, Fadly (Universitas Hamzanwadi, 2026)
Ethnozootherapy, as a component of traditional medical practices, highlights the use of animals or animal-derived products to treat physical ailments, enhance vitality, and fulfil spiritual needs. This research aims to understand the forms of animal use as traditional medicine, examine the cultural values ​​and beliefs of the community that underlie these practices, and analyze the dynamics of local knowledge, including changes in practices amidst the influence of modern medicine and efforts to maintain ecological sustainability. Employing a qualitative approach, data were collected through observation, in-depth interviews, and documentation involving traditional healers and community members who use animal-based remedies. The findings reveal that animals such as snakes, eels, leeches, black chickens, monitor lizards, snakehead fish, and wild bees are used to address diverse health complaints based on empirical knowledge, symbolic interpretations, and spiritual beliefs. These practices not only constitute a traditional healing system but also function to maintain social structure, reinforce cultural identity, and facilitate intergenerational knowledge transmission. Amid the growing presence of modern medical services, communities selectively adapt by retaining practices perceived as effective and safe. Furthermore, the use of local ecological wisdom demonstrates an embedded ethical awareness supporting sustainable resource use. Thus, ethnozootherapy plays an essential role in both local health systems and the cultural continuity of the Kualu community.